Shizao decoction for cirrhotic ascites: assessing potential targets based on network analysis combined with pharmacokinetics and metabolomics - Li, Wenjing; Hou, Yujiao; Wang, Yanping; Liu, Ronghong; Zhang, Han; Luo, Yanqiong; Li, Qian; Njolibimi, Mosesmanaanye; Hong, Bo; Xu, Tao (Frontiers in Pharmacology, 2024)
Shizao decoction (SZD) is a traditional Chinese medicine decoction that has therapeutic effects on cirrhotic ascites (CAS). Because of the unclear treatment mechanism, in the current study, the anti-CAS activity of SZD and molecular mechanisms were analyzed by network analysis combined with pharmacokinetics and metabolomics. Firstly, we assessed the anti-CAS efficacy of SZD by hematoxylin-eosin (H&E), liver function tests, NO and ET-1 levels, and portal venous pressure. Secondly, network analysis was applied to dig out the metabolites, targets, and pathways related to SZD and CAS. Then, the pharmacokinetics of the pharmacokinetically relevant metabolites (PRM) were analyzed. Thirdly, the serum and urine metabolic biomarkers of rats with CAS were identified using metabolomics by comparing them with the SZD treatment group. In addition, MetaboAnalyst was utilized to conduct metabolic pathway analysis. Finally, the correlation analysis established a dynamic connection between absorbed PRM from SZD and CAS-associated endogenous metabolites. Pharmacodynamic analysis indicated that SZD effectively mitigated liver injury symptoms by ameliorating inflammatory cell infiltration in CAS rats. The network analysis results indicated that twelve RPM contribute to the therapeutic efficacy of SZD against CAS; the key signaling pathways involved might be hepatitis B and PI3K-Akt. Pharmacokinetics results showed that the 12 RPM were efficiently absorbed into rat plasma, ensuring desirable bioavailability. The metabolomic analysis yielded 21 and 23 significantly distinct metabolites from the serum and urine, respectively. The 12 bioavailable SZD-PRM, such as luteolin, apigenin, and rutin, may be associated with various CAS-altered metabolites related to tryptophan metabolism, alpha-linolenic acid metabolism, glycine metabolism, etc. A novel paradigm was provided in this study to identify the potential mechanisms of pharmacological effects derived from a traditional Chinese medicine decoction.